2007
DOI: 10.1186/1479-5868-4-18
|View full text |Cite
|
Sign up to set email alerts
|

The school food environment and adolescent obesity: qualitative insights from high school principals and food service personnel

Abstract: ObjectivesTo examine high school personnel's perceptions of the school environment, its impact on obesity, and the potential impact of legislation regulating schools' food/beverage offerings.MethodsSemi-structured interviews were conducted with the principal (n = 8) and dietitian/food service manager (n = 7) at 8 schools (4 rural, 4 suburban) participating in a larger study examining the relationship between the school environment and adolescent health behavior patterns.ResultsPrincipal themes included: 1) Obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 31 publications
5
59
0
Order By: Relevance
“…Political support, top-down through policies and resources, can help to set standards and priorities for health promotion activities (Sabatier, 1997;Tang et al, 2009); however, increasing pressures and demands on the school system create a paradoxical challenge for schools to support school health interventions and policy initiatives (Nollen et al, 2007;Evenson et al, 2009;Kelder et al, 2009;MacLellan et al, 2009;Langille and Rodgers, 2010). Consistent with recent literature (Amis et al, 2012), the participants in the current study reported that increasing demands on teachers and principals limited the overall support that a school could provide to health promotion activities.…”
Section: Discussionsupporting
confidence: 78%
“…Political support, top-down through policies and resources, can help to set standards and priorities for health promotion activities (Sabatier, 1997;Tang et al, 2009); however, increasing pressures and demands on the school system create a paradoxical challenge for schools to support school health interventions and policy initiatives (Nollen et al, 2007;Evenson et al, 2009;Kelder et al, 2009;MacLellan et al, 2009;Langille and Rodgers, 2010). Consistent with recent literature (Amis et al, 2012), the participants in the current study reported that increasing demands on teachers and principals limited the overall support that a school could provide to health promotion activities.…”
Section: Discussionsupporting
confidence: 78%
“…The findings are likely to be relevant outside of New Zealand, when considering school food environments across socioeconomic and geographic contexts. The barriers identified generally echo those expressed in other studies, especially related to resources to implement changes, and the role of food sales in fundraising 32,33,35 . Williden et al 34 , in a different region of New Zealand, identified the barriers to healthy eating as: the cost of food; availability of healthy food; children's food preferences; and nutrition knowledge of parents.…”
Section: Discussionmentioning
confidence: 60%
“…Prior research has revealed several barriers to healthy eating, including convenience and low cost of less nutritious fast food (Croll et al 2001; Cullen et al 2007; Drewnowski and Specter 2004), lack of availability and high cost of healthier food (Harrison 2005; McKinley et al 2005; Monsivais and Drewnowski 2007), and perceived need by school staff to provide tastier, less healthy food to maintain student participation in cafeteria programs (Bauer et al 2004; Nollen et al 2007). Youth have cited a preference for unhealthy food (including fast food) due to the perception that healthy food looks less appealing and tastes worse (Evans et al 2006; Harrison 2005; Shepherd et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Youth have cited a preference for unhealthy food (including fast food) due to the perception that healthy food looks less appealing and tastes worse (Evans et al 2006; Harrison 2005; Shepherd et al 2006). In schools, staff and students note easy vending machine access (Cullen et al 2007; Nollen et al 2007) and inadequate funding for food services to provide healthier food (Cullen et al 2007). Social pressure, such as peers’ teasing, may prevent students from eating healthy foods at school, including meals served through the National School Lunch Program, the federally subsidized program with nutritional content standards (Bauer et al 2006; Cullen et al 2007; Nollen et al 2007), and food brought from home that may potentially be healthier than some other options (Croll et al 2006; Evans et al 2006).…”
Section: Introductionmentioning
confidence: 99%